2006
DOI: 10.3354/meps328267
|View full text |Cite
|
Sign up to set email alerts
|

Relative predation vulnerability of three juvenile (Age-0) North Pacific flatfish species: possible influence of nursery-specific predation pressures

Abstract: Pleuronectid flatfish are generally thought to utilize stereotypical anti-predator behavior to reduce encounters with potential predators. In this study, we tested the relative vulnerability of 3 juvenile (Age-0) flatfish species to predation under controlled laboratory conditions. Predators consumed significantly more English sole Parophrys vetulus than either Pacific halibut Hippoglossus stenolepis or northern rock sole Lepidopsetta polyxystra in clear water (0 nephelometric turbidity units, NTU), suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…When lying flat on the sediment, their low body profile and ability to cryptically match the color and texture of sediments, as well as bury in it (Ramachandran et al, 1996;Ellis et al, 1997;Healey, 1999), renders them nearly invisible to approaching predators and/or prey. Upon detecting an approaching predator, flatfish cease movement (Burrows and Gibson, 1995;Burrows et al, 1994;Lemke and Ryer, 2006a) and are reticent to flee unless the predator gets very close (Ryer et al, 2004b;Lemke and Ryer, 2006b). In contrast, many of the roundfish that are targeted by trawl fisheries (e.g.…”
Section: Flatfish Anti-predator Behaviormentioning
confidence: 95%
“…When lying flat on the sediment, their low body profile and ability to cryptically match the color and texture of sediments, as well as bury in it (Ramachandran et al, 1996;Ellis et al, 1997;Healey, 1999), renders them nearly invisible to approaching predators and/or prey. Upon detecting an approaching predator, flatfish cease movement (Burrows and Gibson, 1995;Burrows et al, 1994;Lemke and Ryer, 2006a) and are reticent to flee unless the predator gets very close (Ryer et al, 2004b;Lemke and Ryer, 2006b). In contrast, many of the roundfish that are targeted by trawl fisheries (e.g.…”
Section: Flatfish Anti-predator Behaviormentioning
confidence: 95%
“…Increased turbidity is often a result of increased concentration of suspended particles (Davies‐Colley & Nagels, 2008; Nieman, Oppliger, McElwain, & Gray, 2018). Increased turbidity decreases the ability of visually oriented predators to see their prey (Higham, Stewart, & Wainwright, 2015; Ranåker, Nilsson, & Brönmark, 2012; Sweka & Hartman, 2003; Turesson & Brönmark, 2007), which negatively influences their prey consumption (Figueiredo et al., 2019; Sweka & Hartman, 2003). The reduced efficiency in capturing prey in turbid waters of visually oriented predators may even result in their low abundance and local extinction (dos Santos et al., 2017; Manning, Mayer, Bossenbroek, & Tyson, 2013; Tejerina‐Garro, Fortin, & Rodríguez, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When faced with predation risk, they behave more like rock sole. Standardized predation trials indicated that English sole were the most vulnerable to predation, rock sole the least, and halibut were intermediate between the other 2 species (Lemke & Ryer 2006b.…”
Section: Introductionmentioning
confidence: 94%